(3JfHjg GdYbhd Ydi JfRjg GdUhajI Yf GYJbGO GdJLSje hGdYjfjI hGdEJMGO hGdMdhds - (3HQgGf GdOjf YHO Gddg EHQGgje Hf MSf GdcQOi GdchQGfi GdTgQRhQi GdSgQGfi Ke GdeOfj,J (B1101 (3g` s ((3CMeO CHj UGdM GdYeQhSi GdeGdci GdhaGFi s)
(3ChdgG (B:s
(3CeG HYO abO UM Yf GdfHi Udi Gddg Ydjg hSde Cfg bGd GdEjeGf HVY hSHYhf TYHI CaVdgG bhd dG Edg EdG Gddg hCOfGgG EeGWI GdCPi Yf GdWQjb s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde Ef ef CaVd EjeGf GdeQA Cf jYde Cf Gddg YR hLd eYg MjK cGf GfJgi hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY WdYJ (B_ (3JhMjO (B585) s
Keywords: (3GdJhMjO hGdedd hGdfMds